PENGARUH KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Hayati, Rita; Arafat, Yasir; Sari, Artanti Puspita (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This study aimed at determining the effect of organizational commitment and work motivation on teacher performance. This research uses quantitative methods with correlational type of research. The population of this study was 44 people, namely teachers of Sungai Rotan 1 High School. The sampling technique in this study is the census (quota) so that the entire population is sampled. Data collection techniques using a questionnaire. Data were analyzed using correlation analysis techniques and multiple linear regression. The results showed that: (1) organizational commitment had a positive and significant effect on the performance of Sungai Rotan 1 High School teachers; (2) work motivation has a positive and significant effect on the performance of teachers at Sungai Rotan 1 High School; and (3) organizational commitment and work motivation together have a positive and significant effect on the performance of Sungai Rotan 1 High School teachers. The conclusion of this study is that to improve teacher performance, organizational commitment and work motivation are needed.